Validation of the Dutch leakage score as a predictor of anastomotic leakage in intestinal surgery in a third level hospital - Barker-Antonio, Alan; Jarquin-Arremilla, Arturo; Cruz, Elias Hernandez; Garcia-Manzano, Roberto Armando; Davila-Ruiz, Ediel Osvaldo (International Journal of Research in Medical Sciences, 2021)
Background: Intestinal surgery can present multiple complications that can lead to patient death; therefore, it is important to design early detection strategies to reduce complications in patients with intestinal anastomosis and thus avoid patient death. The aim of this work is to evaluate the diagnostic performance of the Dutch leakage score in 125 patients with intestinal anastomosis as a predictor of anastomotic leakage. Methods: In a sample of 125 patients undergoing intestinal anastomosis, demographic variables were identified and the Dutch leakage score was applied. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were obtained using a 2×2 table. Results: The Dutch leakage score was positive in 23.2% (29 patients) of whom 24 had anastomotic leakage and 5 had no anastomotic leakage. It presents a sensitivity in the test of 100%, a specificity of 95%, a positive predictive value of 82.7%, a negative predictive value of 100%. The diagnostic accuracy is 96%. Conclusions: The Dutch leakage score is a versatile tool, inexpensive, easy to apply and available in any hospital center. It is capable of early diagnosis of anastomotic leakage. It favors early re-intervention, improves prognosis and survival, decreases hospital stay and health care costs.